Calidad de vida relacionada a la salud (cvrs) y sus factores asociados en los pacientes en hemodiálisis crónica de la Red Asistencial Huánuco – Essalud 2013 - Tucto berrios, Joel (2019)
Objective: Assessing the health related quality of life (HRQOL), describe its dimensions and explore their probable association with hemoglobin, serum albumin and adherence to treatment in patients in chronic hemodialysis in the Huánuco Healthcare Network - EsSalud. Methods: An observational, descriptive, prospective study, case series. It was assessed the HRQOL in 39 patients with chronic hemodialysis using the KDQOL-SF questionnaire. Data were collected sociodemographic, clinical and laboratory. It was assessed adherence to treatment. Bivariate associations were explored. Results: The average age was 51.44±17.81 years old. 59% were not-adherent. In the HRQOL analysis, the total score was 54.14±12.14; the dimensions with the highest scores were symptoms/problems (78.47±6.91) and the attitude of the staff of hemodialysis (75.64±5.44) mental health (71.79 ± 8.75) and with the lowest scores is cognitive function (28.93 ± 9.75) physical role (23.07±5.53) and quality of social  relationships (20.00±8.89). It was found a relationship between the level of hemoglobin and emotional role (rs=0.326, p=0.042), the non-adherent have higher scores on the dimensions general health (51.73±16.96 vs. 39.06±15.72 p=0.023), PCS (52.22±17.28 vs. 40.35±14.44 p=0.030) and the social function (73.91±20.26 vs. 53.12±33.38 p=0.020). It was not found a significant relationship with respect to albumin. Conclusions: The population in study has a better HRQOL in the dimensions, symptoms and problems, hemodialysis staff attitude, mental health and worse HRQOL cognitive function, physical role and quality of social relationships. Higher hemoglobin in the emotional role score increases. Besides, being non-adherent is associated with better general health scores, PCS and social function.